Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/su10113971
|View full text |Cite
|
Sign up to set email alerts
|

Low-Emission Modeling for Energy Demand in the Household Sector: A Study of Pakistan as a Developing Economy

Abstract: In the developing world, the energy needs of the household sector have grown manifold, due to rapid urbanization and the introduction of affordable technology. However, constraints in the power supply and underutilization of renewable resources, coupled with inefficient fuel use and obsolete technology, have increased the average energy usage cost and emissions. Hence, the current study provides a long-term sustainable energy management plan for the urban household, in terms of energy savings, social cost, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Energy is the backbone of economic growth and development and high energy consumption is considered a parameter to judge the standard of living in the world. An increase in energy consumption is generally regarded as a positive indication of economic prosperity; however, growing energy consumption leads to growing levels of GHGs and atmospheric pollution . In the recent past, a majority of GHGs were emitted by the energy sector, out of which CO 2 emissions were the most hazardous ones generating from fossil fuel consumption…”
Section: Overview Of Sectorial Ghg Emissions In Pakistanmentioning
confidence: 99%
See 1 more Smart Citation
“…Energy is the backbone of economic growth and development and high energy consumption is considered a parameter to judge the standard of living in the world. An increase in energy consumption is generally regarded as a positive indication of economic prosperity; however, growing energy consumption leads to growing levels of GHGs and atmospheric pollution . In the recent past, a majority of GHGs were emitted by the energy sector, out of which CO 2 emissions were the most hazardous ones generating from fossil fuel consumption…”
Section: Overview Of Sectorial Ghg Emissions In Pakistanmentioning
confidence: 99%
“…An increase in energy consumption is generally regarded as a positive indication of economic prosperity; however, growing energy consumption leads to growing levels of GHGs and atmospheric pollution. 39 In the recent past, a majority of GHGs were emitted by the energy sector, out of which CO 2 emissions were the most hazardous ones generating from fossil fuel consumption. 40 For the near future, greater demand for energy and increased consumption is a perspective issue.…”
Section: Overview Of Sectorial Ghg Emissions In Pakistan Ghg Emissionmentioning
confidence: 99%
“…which contributed an overall 80% of CO 2 and two third of GHGs. The World Bank reported that during that era, the US posed the least impact due to increased renewable share in energy-mix (Bashir et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The estimations of the demand side scenario show that efficient water heating can save more electricity than cooling. Moreover, renewable energy use in electricity production can mitigate CO 2 emission significantly [55].…”
Section: Literature Reviewmentioning
confidence: 99%